Law No. 153 Of The Year 2022 On Waiving The Delay Charge And Additional Tax, And Prolonging The Enforcement Of Law No. 79 Of The Year 2016 On The Termination Of Tax Disputes = قانون رقم 153 لسنة 2022 بالتجاوز عن مقابل التأخير والضريبة الإضافية وبتجديد العمل بالقانون رقم 79 لسنة 2016 فى شأن إنهاء المنازعات الضريبية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic